Donor Parameters and Platelet Yield during Plateletpheresis: A Cross-sectional Prospective Study - Ruchi Singh; Ganga S. Pilli; Ramadevi Vivek Wani (Journal of the Scientific Society)
Background: Platelet transfusion can be life-saving in bleeding patients with thrombocytopenia or reduced platelet function. Single donor platelets (SDP) unit use is preferred due to the various advantages like reduction in transfusion-transmitted diseases and transfusion reactions. The quality of SDP is determined by platelet yield. Therefore, we conducted this study to assess the donor parameters affecting platelet yield during plateletpheresis. Materials and Methods: This cross-sectional prospective study included 160 single-donor platelet apheresis procedures done for 1 year. The pre-donation platelet count of the donor was set to 250 × 109/L to get double-dose platelet. Plateletpheresis was performed using Trima Accel single-needle separator apheresis machine. The demographic and hematologic parameters of donors were correlated with their platelet yield. Data obtained were tabulated using version 20 of the Statistical Package for the Social Sciences (SPSS). A relationship between pre-donation donor variables and platelet yield was studied using the Pearson correlation coefficient (r). P < 0.05 was considered statistically significant. Results: There was a significant positive correlation between platelet yield and body mass index (BMI) (r = 1710 and P = 0.0304), total leukocyte count (TLC) (r = 0.2220 and P = 0.0048), and platelet count (r = 0.8880 and P < 0.0001). The mean platelet volume (MPV) showed a negative correlation with platelet yield (r = −0.1910 and P = 0.0156). Age, hemoglobin, hematocrit, and platelet distribution width showed no significant correlation with the platelet yield. Conclusion: Donor parameters such as pre-donation platelet count, BMI, TLC, and MPV need to be considered while recruiting the donors for the SDP procedure for better yield of platelets.